Analysis of adoption and impacts of improved maize varieties in Eastern Zambia - Khonje, M.; Manda, J.; Alene, Arega D.; Kassie, M. (Elsevier, 2015)
This paper analyzes the adoption and welfare impacts of improved maize varieties in eastern Zambia using data obtained from a sample of over 800 farm households. Using both propensity score matching and endogenous switching regression models, the paper shows that adoption of improved maize leads to significant gains in crop incomes, consumption expenditure, and food security. Results further show that improved maize varieties have significant poverty-reducing impacts in eastern Zambia. The paper concludes with implications for policies to promote adoption and impacts of modern varieties in Zambia.